Pembelajaran Cerpen Bermuatan Karakter Islami dengan Model Deep Learning di Sekolah Menengah Pertama - Fitri Nur Rahmawati; Chafit Ulya (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2026)
Deep learning g has become a priority approach in the implementation of the Merdeka Curriculum because it emphasizes meaningful, reflective, and student-centered learning. This study aims to describe and analyze the planning, implementation, assessment, challenges, and strengthening efforts of deep learning in short story learning with Islamic character values at SMP Al-Qolam Muhammadiyah Gemolong. The short stories used in this learning specifically contain Islamic character values—such as honesty, courage grounded in morality, responsibility, and piety—which are distinctive features of learning in Islamic-based schools. The research employed a qualitative approach using a case study method. Data were collected through document analysis, classroom observations, and in-depth interviews with teachers, students, and the vice principal for curriculum affairs. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that short story learning with Islamic character content has incorporated the principles of mindful learning, meaningful learning, and joyful learning through discussions, reflections, text analysis, and the use of digital media connected to students' real-life experiences. The implementation of deep learning not only enhanced student engagement, critical thinking, and reflective abilities but also contributed to strengthening Islamic character through the internalization of moral, religious, and social values embedded in literary texts. However, its implementation still faces challenges related to teacher readiness, assessment practices, students' literacy interest, and limited instructional time and learning resources.